1999
DOI: 10.1097/00000658-199912000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Thoracoscopic Splanchnicectomy: Effects on Pancreatic Pain and Function

Abstract: ObjectiveTo evaluate prospectively the effect of bilateral thoracoscopic splanchnicectomy on pancreatic pain and function. Summary Background DataSevere pain is often the dominant symptom in pancreatic disease, despite a wide variety of methods used for symptom relief. Refinement of thoracoscopic technique has led to the introduction of thoracoscopic splanchnicectomy in the treatment of pancreatic pain. MethodsForty-four patients, 23 with pancreatic cancer and 21 with chronic pancreatitis, were included in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 20 publications
(26 reference statements)
0
51
0
Order By: Relevance
“…There was information about the percentage with effective pain relief at 2 weeks but not 2 months. Our initial sample size calculation was therefore based on the observations that opioid treatment had achieved good pain relief in the first 2 weeks in an estimated 70% of patients [1], and CPB or TS gives good pain relief immediately in 90% of patients [14,16]. A Bonferroni correction was included for 3 pairwise comparisons (α = 0.016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was information about the percentage with effective pain relief at 2 weeks but not 2 months. Our initial sample size calculation was therefore based on the observations that opioid treatment had achieved good pain relief in the first 2 weeks in an estimated 70% of patients [1], and CPB or TS gives good pain relief immediately in 90% of patients [14,16]. A Bonferroni correction was included for 3 pairwise comparisons (α = 0.016).…”
Section: Methodsmentioning
confidence: 99%
“…TS has not been studied as extensively as CPB, but on theoretical grounds it is likely that the complications of transient hypotension and diarrhoea would be as frequent as with CPB. Other side effects reported from thoracoscopy include arterial bleeding requiring thoracotomy [14], chylothorax [15] and lung injury causing pneumothorax-requiring drainage.…”
Section: Introductionmentioning
confidence: 99%
“…The operations were performed according to the procedure initially presented by Cuschieri and Ihse (12,14). The primary disease was diagnosed during a preceding laparotomy with pathological confirmation of cancer.…”
Section: Methodsmentioning
confidence: 99%
“…In one study that included only patients with nonalcoholic pancreatitis, those who have had prior surgical or endoscopic interventions had a poorer response in pain relief compared to patients without prior intervention [113]. On the contrary, two other studies involving mostly patients with alcoholic pancreatitis, found no correlation between the success rate of splanchnicectomy and the incidence of prior interventions directed at pain control [111,112]. Although bilateral thoracoscopic splanchnicectomy is safe, involves a minimal access approach, and may provide improved quality of life in patients with small-duct pancreatitis, further studies are needed to identify clearly the appropriate candidates for this procedure [113].…”
Section: Neural Blockmentioning
confidence: 99%
“…A prospective, randomized study comparing the efficacy of EUS-guided versus CT-guided celiac plexus block failed to show any advantage of either approach [110]. Bilateral thoracoscopic splanchnicectomy has been suggested to be the best surgical approach to splanchnic nerve ablation in patients with intractable pain from chronic pancreatitis [111][112][113][114]. In a prospective, semirandomized, case-control study, videothoracoscopic splanchnicectomy significantly decreased intensity of pain and improved the quality of life [114].…”
Section: Neural Blockmentioning
confidence: 99%